The interferon regulatory factor 6 promotes cisplatin sensitivity in colorectal cancer. Issue 4 (1st April 2022) - Tan, Lin; Qu, Weiming; Wu, Dajun; Liu, Minji; Ai, Qiongjia; Hu, Hongsai; Wang, Qian; Chen, Weishun; Zhou, Hongbing
ABSTRACT: Colorectal cancer (CRC) is one of the most common malignancies and causes of cancer-related mortality worldwide. Cell proliferation and tumor metastasis as well as chemoresistance are correlated with poor survival of CRC. The interferon regulatory factor 6 (IRF6) is functioned as a tumor suppressor gene in several cancers and is associated with risk of CRC. We explored the role of IRF6 in CRC in the present study. The protein expressions of IRF6 in human CRC tissues, normal para-carcinoma tissue and liver metastases from CRC were measured. Cell proliferation, chemotherapeutic sensitivity, cell apoptosis, migration and invasion including the related markers along with IRF6 expression were explored. Our results indicated that IRF6 expression in CRC and liver metastasis were lower than normal tissues, which were correlated positively with E-cadherin and negatively with Ki67 expression in CRC tissue. IRF6 promoted CRC cell sensitivity to cisplatin to suppress cell proliferation, migration and invasion as well as aggravate cell apoptosis. Our study suggested that IRF6 may enhance chemotherapeutic sensitivity of cisplatin mediated by affecting cell proliferation, migration and invasion along with apoptosis through regulating E-cadherin and Ki67, while the identified molecular mechanisms remain to be further explored. GRAPHICAL ABSTRACT: uf0001